2019
DOI: 10.35940/ijitee.l3110.1081219
|View full text |Cite
|
Sign up to set email alerts
|

Protein Extraction from Spirulina Platensis

Abstract: The extraction of protein from green spirulina microalgae platensis was carried out by centrifugation, ultra sound assisted extraction and combination of centrifugation and ultrasound assisted extraction spirulina platensis was carried out using ultrasound-assisted extraction and statistical optimization method is used to obtain the optimum conditions. A Box–Behnken design method was used to optimize the process conditions affecting protein extraction. This conditions investigated on microalgae cell disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Moreover, DenBesten and Li 40 reported that the inhibition of protein synthesis produced by fluoride toxicity during enamel development was responsible for dental fluorosis in the incisors of the animals. Hence, the beneficial effect of Spirulina platensis in increasing the level of plasma proteins in this work can be explained by its high crude protein content 41 , 42 . The term crude proteins refer to the total protein content in Spirulina platensis without further refinement or processing, a standard metric in nutritional analysis encompassing all forms of proteins without distinguishing types or quality.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, DenBesten and Li 40 reported that the inhibition of protein synthesis produced by fluoride toxicity during enamel development was responsible for dental fluorosis in the incisors of the animals. Hence, the beneficial effect of Spirulina platensis in increasing the level of plasma proteins in this work can be explained by its high crude protein content 41 , 42 . The term crude proteins refer to the total protein content in Spirulina platensis without further refinement or processing, a standard metric in nutritional analysis encompassing all forms of proteins without distinguishing types or quality.…”
Section: Discussionmentioning
confidence: 75%
“…Amino acids are very important due to help build muscles, blood and internal organs (Al Hinai et al 2019). The data in Table (2) show the percentage of amino acids content of A. plantesis.…”
Section: Amino Acids and Nutraional Value Of Phycobiliprotein Extract...mentioning
confidence: 99%
“…One of the aims for growing Spirulina was to produce a new source of complete food supplement for a starving planet. One tablespoon per day has major health benefits (Al Hinai et al, 2019). The growth in the world's population and forecasts of a protein crisis in the early 1950s sparked a search for new complementary and unconventional protein sources (de Morais et al, 2019).…”
Section: Althoughmentioning
confidence: 99%